Automatic programmable air ozonizer - Gubarev, S.P.; Klosovsky, A.V.; Opaleva, G.P.; Taran, V.S.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2015)
In this paper we describe a compact, economical, easy to manage auto air ozonator developed at the Institute of Plasma Physics of the NSC KIPT. It is designed for sanitation, disinfection of premises and cleaning the air from foreign odors. A distinctive feature of the developed device is the generation of a given concentration of ozone, approximately 0.7 maximum allowable concentration (MAC), and automatic maintenance of a specified level. This allows people to be inside the processed premises during operation. The microprocessor controller to control the operation of the ozonator was developed. Описан разработанный в Институте физики плазмы ННЦ ХФТИ малогабаритный, экономичный, простой в управлении автоматический воздушный озонатор. Он предназначен для санации, дезинфекции помещений и очистки воздуха от посторонних запахов. Отличительной особенностью разработанного прибора является генерация озона заданной концентрации (порядка 0,7 ПДК) и автоматическое поддержание заданного уровня. Это позволяет людям безопасно находиться внутри обрабатываемых помещений во время работы прибора. Управление работой озонатора осуществляется с помощью разработанного в Институте физики плазмы ННЦ ХФТИ микропроцессорного контроллера. Описано розроблений в Інституті фізики плазми ННЦ ХФТІ малогабаритний економічний, простий в управлінні автоматичний повітряний озонатор. Він призначений для санації, дезинфекції приміщень і очищення повітря від сторонніх запахів. Відмінною особливістю розробленого приладу є генерація озону заданої концентрації (порядку 0,7 ГДК) та автоматична підтримка заданого рівня. Це дозволяє людям перебувати безпечно всередині оброблюваних приміщень під час роботи приладу. Управління роботою озонатора здійснюється за допомогою розробленого в Інституті фізики плазми ННЦ ХФТІ мікропроцесорного контролера.